Broadband beam scanning circularly‐polarised leaky‐wave antenna based on modified substrate integrated waveguide. Issue 5 (1st February 2013) - Jin, C.; Mujumdar, M.; Alphones, A.
Abstract : A high gain broadband beam scanning circularly‐polarised (CP) leaky‐wave antenna (LWA) is proposed based on a modified substrate integrated waveguide. The designed CP LWA has been fabricated and its performance measured. The reported antenna presents expected broadband matched impedance with a measured reflection coefficient | S 11 | < − 10 dB from 15.4 to 19 GHz. The radiation pattern was measured and the axial ratio of the antenna is within 3 dB from 15.9 to 17.2 GHz. The antenna exhibits continuous beam scanning from 35° at 15.5 GHz to 47° at 18 GHz according to the broadside with maximum gain of 12.3 dBi.